The impact of gender differentiation in the social media influencer toward skin care advertisement - Chuah, Jing Mun; Wang, Wei Gi (2020)
In this modern era, advertisement has been considered as an essential tool for the marketers to identify themselves in the concentrated marketplace as well as to influence the potential consumers especially through the platform of social media. Nowadays, the social media have penetrated into our daily life to influence us with various ideas, thoughts, attitudes or more specifically to state that it could influence our purchase intention too. Therefore, the social media influencers act as an important role to spread some ideas and bring a significant impact to their followers. However, there might be some differences based on the gender differences of the social media influencers. This study examined the impact of gender differentiation in the social media influencers toward skin care advertisements. Quantitative research will be used in the study. There are 311 students of Faculty Arts and Social Science from Universiti Tunku Abdul Rahman (UTAR), Kampar campus will be selected in the quantitative section of this study. The online survey will be chosen and distributed to the eligible participants through online class and email. Quantitative data will be analyzed by using the Pearson Correlation Coefficient to determine the relationship between the gender differentiation of social media influencers’ trustworthiness, expertise, and attractiveness on skin care advertisement. Moreover, the independent samples t-Test will be used to identify whether male or female social media influencers have more effect toward skin care advertisements.